Engaging China: factor and their relationship towards successful market / Abdul Hakam Ibrahim - Ibrahim, Abdul Hakam (Faculty of Business and Management, 2011)
China is one of the fastest growing markets in the world especially in Asia. Since China open their market, there a lot of success and failure story of doing business in this developing nation. The purpose of this research is to explore the relationship between successful market entry with the factor of entry modes, country risk and cultural distance. Furthermore, researcher also going to identify which factor the most significant factor that influenced the success rate of doing business in China market.